PS 08-16 LEFT VENTRICULAR DIASTOLIC DYSFUNCTION AS A PREDICTOR OF THE NONVALVULAR ATRIAL FIBRILLATION. (September 2016) - Music, Ljilja; Knezevic, Bozidarka; Bulatovic, Nebojsa
Abstract : Objective: The aim of the stady was to determine whether diastolic dysfunction is associated with increased risk of nonvalvular atrial fibrillation (NVAF) in adults with no history of atrial arrhythmia. Clinical studies of diastolic dysfunction and the risk of NVAF in populations without structural heart disease suggest that diastolic dysfunction and LA dilation may represent important mechanisms of disease. Design and Method: A total of 583 individuals with arterial hypertension have participated in the trial Damage to the heart muscle and occult coronary disease in asymptomatic hypertensive patients. All patients were examined by echocardiography (M-mode, two-dimensional, pulse and tissue Doppler). The clinical and echocardiographic characteristics of patients which were examined 2011. were reviewed 2014. Exclusion criteria were the history of ischemic heart disease, atrial arrhythmia, valvular or congenital heart disease, pacemaker implantation, stroke. Results: Of 583 patients (54% men, age 62 ± 6.4years), 6.9% patients had ejection fraction (EF) ⩽ 45%. Diastolic dysfunction (DD) (E/A > 0.74) was discovered in 350 (60%) patients. 409 (70, 1%) patients had E/Ea index > 8. Left atrial (LA) enlargement and E/Ea index were significant for DD (p = 0.017 vs. p = 0, 018 respectively). Index E/A was significantly influenced by duration of hypertension (p = 0, 017). Over a mean follow-up of 3.1 ± 1.2 years, 57 (9.7%) persons developed NVAF. DD, LA size and E/Ea index as well as duration of hypertension, were the most important factors for prediction of NVAF. Conclusions: Diastolic dysfunction presents a potentially important link between many common risk factors, such as hypertension, age, obesity, diabetes mellitus, and the development of AF. Further research into both treatment of diastolic dysfunction and methods for noninvasive assessment are needed to explain this connection.